Ways of presenting and analising large amounts of visual data - Боцюра, І. С. (ХНУРЕ, 2021)
We live in a visual society. Millions of photos are uploaded to the World Wide Web every day. Nevertheless, for a long time the role of images in the era of big data was underestimated, not given the necessary attention. Nowadays, certain media visualization techniques have already been invented for a large number of images, which facilitate their analysis, help find patterns, dynamics in a broad context. Here are some of them.
Науковий керівник – асистент Терещенко Г.Ю.
Keywords: ways of analising; visual data